Application of Cassava Slicer Machine and Oil Dryer Machine in Micro Enterprises in Simalungun District - tafsin, maruf (Journal of Saintech Transfer, 2019)
Cassava chips are one of the types of snacks that are in the public interest. So this is a market object that is quite promising by entrepreneurs. But they must compete in quality and taste. So far, slicing cassava and draining cassava chips produced manually so that the results are less than optimal and from this problem where become the starting point to solve solution to the micro-enterprises . The method used in carrying out this training consists of several methods, namely: (1) Survey to the place of partners in the micro business group in Simalungun. This survey is the initial stage of the activity, which in this activity aims to see firsthand the problems faced. This survey stage is very crucial to get the right solution to the problems that exist. (2) Prequestionnaire this activity is carried out to see how far partners understand how vital the operation and maintenance of the machine. (3) Preparation of cassava slicing machines, this stage consists of several parts including the design of tools that suit the needs of partners, this needs to carry out so that the appropriate equipment specifications obained. (4) Application of equipment and process analysis, this stage is carried out at the partner's place, this stage demonstrates the use of cassava slicing machines to partners so that the results of a direct analysis are seen to increase the efficiency of the use of machinery to the production process. (5) Counseling to partners, this extension activity is significant to be carried out as part of community service. This extension is done to transfer technology to partners in terms of the use and maintenance of the machines provided; (6) Post questionnaire, the questionnaire activity at the end of the devotion activity aims to measure whether the problem faced by the partner has been resolved, and see the increase in the benefits of the machine being donated.